Drop vertical jump performance and asymmetries in young rhythmic gymnasts - Passacantando, E.; Marinelli, S.; La Greca, S.; Farina, F.; Cariati, I.; Cifelli, P.; Di Giminiani, R. (Sports Biomechanics, 2025)
Rhythmic gymnastics (RG) is an Olympic discipline that emphasises repetitive unilateral movements that may lead to musculoskeletal asymmetries. The present study aimed to investigate the lower limb asymmetries during drop vertical jumps (DVJs) in young RG athletes. Fifteen young RG athletes (Age: 12.15 ± 2.26 years; Stature: 148.89 ± 14.31 cm; Body Mass: 39.02 ± 12.26 kg; BMI: 17.11 ± 2.65 Kg/m2), performed DVJs by stepping off a box using their preferred and non-preferred limbs. Several performance variables (flight time, contact time, reactive strength index-RSI, power output) and specific peaks of the vertical ground reaction force (vGRF)-time profiles in distinct jump phases for each limb, were analysed. When athletes stepped off the box with their preferred limb, the concentric force generation (the third peak of vGRF) was significantly higher in the preferred than the non-preferred limb (p < 0.05). Conversely, when athletes stepped off with the non-preferred limb, the force absorption during the breaking phase (the second peak of vGRF) was higher in the non-preferred limb than in the preferred limb (p < 0.01). The asymmetries observed in force parameters highlight the impact of RG`s training demands. Addressing asymmetries in RG training may promote musculoskeletal health. Future research should explore the neural mechanisms underlying these asymmetries.